2021
DOI: 10.3389/fphy.2021.652179
|View full text |Cite
|
Sign up to set email alerts
|

Development of 18F-Labeled Resazurin Derivatives for the Detection of Tumor Metabolic Activity Using Cerenkov Imaging

Abstract: This paper describes functional fluorinated bioactivatable molecules to study cancer metabolism using Cerenkov imaging. Resazurin (RA), or Alamar Blue, is a commonly used viability dye and redox sensor. Under reductive conditions or by the action of NADH dehydrogenases, RA is reduced into resorufin (RAred), a highly fluorescent molecule. Cold- and radiolabeled monofluorinated resazurin (MFRA) and difluorinated resazurin (DFRA) were synthesized using electrophilic fluorination. The fluorescence of the reduced p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In turn, the protein concentration of the media has been noticed to have an effect on the change in form [27]. Later, this dye was applied to study the metabolic characteristics of cells [28] and tumor cells [29]. We applied a similar approach to a resazurin reduction test to cancer detection in urine.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, the protein concentration of the media has been noticed to have an effect on the change in form [27]. Later, this dye was applied to study the metabolic characteristics of cells [28] and tumor cells [29]. We applied a similar approach to a resazurin reduction test to cancer detection in urine.…”
Section: Discussionmentioning
confidence: 99%
“…[76] Functional Cerenkov agent MFRA, an 18 F-labeled Resazurin that can be reduced into highly fluorescent resorufin, reportedly could be used to determine tumor energy imbalance and reductive environments and assess the metastatic potential of tumors. [77] In addition, the feasibility of Cerenkov luminescence tomography (CLT) has been demonstrated. [78] Given that radio-metal ions, such as 90 Y, 89 Zr, and 68 Ga, yield more photons than 18 F, [71a,79] utilizing such radionuclides holds advantages for imaging and related photodynamic therapy.…”
Section: Cerenkov Luminescence Imaging (Celi)mentioning
confidence: 99%
“…Living cells metabolise the non-toxic resazurin, and the process can be monitored through the fluorescence emission of resorufin, which is also harmless to living cells [5]. Translating the application of resazurin from in vitro studies to in vivo methods presents certain difficulties, mainly because the optical properties of resazurin and its reduced form, resorufin, fall outside the near-infrared (NIR) imaging window [37,38]. The NIR imaging window, also known as the phototherapeutic window, is defined by a range of wavelengths where light exhibits greater penetration into body tissues [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Kachur et al [38] reported the synthesis of a new class of compounds, fluorinated resazurin derivatives, aimed at in vivo applications. Arroyo et al [37] tested some of these new compounds for the ex vivo and in vivo detection of tumour metabolic activity using Cerenkov luminescence imaging. Even more ambitious in vivo applications can be envisioned if the direct excitation of resorufin derivatives, inducing its fluorescence emission, is possible in the NIR imaging window.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation